(untitled) (Publications Office, 2023)
The eighth issue of Andina magazine is structured as a multifaceted space for critical reflection where institutional transformation, urgent debates on the current political and technological landscape, and the artistic expressions that define the region’s identity converge. The starting point for this volume is the need to rethink university and academic structures in the post-pandemic era. Through proposals such as the new model of institutional academic reinvention and the design of a Doctorate in Education with an integrative approach, a commitment is evident to forge a flexible pedagogical paradigm adapted to future scenarios, capable of transcending traditional approaches and establishing self-assessment as a driver of continuous, dialogic, and non-punitive development.